Cybercrime - 20160731 frey50; Berlatsky, Noah
Examines the issue of cybercrime from a variety of international perspectives.
Ch. 1: Vulnerability to cybercrime - Increased internet access in South Africa makes it more vulnerable to cybercrime / Charles Goredema -- In Singapore, young adult males are especially vulnerable to cybercrime / Ellyne Phneah -- Women are especially vulnerable to cybercrime in Pakistan / Zofeen Ebrahim -- Cybercrime concerns grow in China / Kathrin Hille -- Canadian banks look to insurance to decrease vulnerability to cybercrime / John Greenwood -- g ch. 2: Law and cybercrime -- Thailand's cybercrime law stifles freedom of speech / Lynette Lee Corporal -- France's cybercrime laws may threaten Internet freedom / Stefan Simons -- Iraq's cybercrime law stifles freedom of speech / Human Rights Watch -- Weak Ukrainian laws allow cybercrime to proliferate / Yuriy Onyshkiv -- Weak laws in Nigeria allow cybercrime to proliferate / David Ashaolu -- In Australia, combating cybercrime should begin by supporting and funding existing organizations / Stilgherrian -- g ch. 3: Organized crime and cybercrime -- Russian cybercrime thrives as Soviet-era schools spawn hackers / Anastasia Ustinova -- Worldwide, cybercrime is committed by organized crime members, not by hackers / John Leyden -- In Mexico, drug cartels are moving into cybercrime / Infosec Institute -- In India, cybercrime is becoming increasingly organized and professional / Priyanka Joshi -- Eastern European organized cybercrime rings prey on victims worldwide -- g ch. 4: Cyber espionage and cyberterrorism -- Worldwide, state-supported cyber espionage is a growing danger / Economist -- The United States and Israel launched a cyber attack upon Iran / Joby Warrick -- Tibetan exiles may be the target of Chinese cyber espionage / Information Warfare Monitor -- The United Kingdom may be targeted by cyberterrorists / Imran Awan.
Keywords: Computer crimes; Computer crimes; Computer crimes